2017
DOI: 10.1002/apj.2158
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of solid acids catalysed nitration of toluene: Change in selectivity by triphase (liquid–liquid–solid) catalysis

Abstract: Nitrotoluenes are precursors to a variety of commercially important products such as dyes, pharmaceuticals, and plastics. The protonated form of Y, ZSM-5, and mordenite zeolites as well as strongly acidic cation exchange resin (Amberlite IR-120) were examined as triphase catalyst (liquid-liquid-solid) for the nitration of toluene to produce mainly mononitrotoluenes. Among the solid acid catalysts tested, zeolites were found to be more active than cation exchange resin with highest activity for H-mordenite foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Henceforth, numerous studies have confirmed the existence of the nitronium ion . The presence of a catalyst facilitates the dissociation of nitric acid, shifting the equilibrium toward the formation of NO 2+ that reacts with the benzene ring to produce nitrotoluene. The basic mechanism is shown in the following equation normalH normalN normalO 3 + H + H 2 normalN normalO 3 + normalN normalO 2 + + H 2 normalO A r H + normalN normalO 2 + normalA normalr + ( H ) normalN normalO 2 normalA normalr normalN normalO 2 + H + …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henceforth, numerous studies have confirmed the existence of the nitronium ion . The presence of a catalyst facilitates the dissociation of nitric acid, shifting the equilibrium toward the formation of NO 2+ that reacts with the benzene ring to produce nitrotoluene. The basic mechanism is shown in the following equation normalH normalN normalO 3 + H + H 2 normalN normalO 3 + normalN normalO 2 + + H 2 normalO A r H + normalN normalO 2 + normalA normalr + ( H ) normalN normalO 2 normalA normalr normalN normalO 2 + H + …”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, numerous studies have confirmed the existence of the nitronium ion. 7 The presence of a catalyst facilitates the dissociation of nitric acid, shifting the equilibrium toward the formation of NO 2+ 8 that reacts with the benzene ring to produce nitrotoluene. The basic mechanism is shown in the following equation …”
Section: Introductionmentioning
confidence: 99%